2003
DOI: 10.1093/sleep/26.8.973
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Eye Movement Density is Reduced in the Normal Elderly

Abstract: The incidence of eye movements during rapid eye movement sleep is substantially reduced in the elderly. We hypothesize that this reduction is due to degenerative (aging) rather than developmental brain changes. The correlation analysis indicates that EMD is a reasonably stable individual trait in both young and elderly adults. These results encourage normative studies of EMD over a wider age span and continued exploration of the relation of EMD to cognitive function in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 32 publications
1
28
1
2
Order By: Relevance
“…The time in REM sleep, on the other hand, remains relatively unchanged in late life. However, there is a significant decrease in the density of phasic REMs in elderly persons (254).…”
Section: Sleep and Memory Formation In Aged Rats And Humansmentioning
confidence: 99%
“…The time in REM sleep, on the other hand, remains relatively unchanged in late life. However, there is a significant decrease in the density of phasic REMs in elderly persons (254).…”
Section: Sleep and Memory Formation In Aged Rats And Humansmentioning
confidence: 99%
“…Of these, the most notable is the increase in nighttime awakenings and the consequent increase in sleep fragmentation (Bliwise, 1993). Some studies have also reported a reduction in slow-wave sleep (SWS) quantity, quality and distribution across sleep (Cajochen et al, 2006; Carrier et al, 2001; Lombardo et al, 1998), as well as a reduction in rapid-eye movement (REM) density (the number of REMs per minute; Darchia et al, 2003). Concurrent with these alterations in sleep is a general decline in episodic memory with age, particularly after the age of 60 yrs (Ronnlund et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…REMs during REM sleep is substantially reduced in the elderly [10] and increased EMG activity has also been reported [11]. These changes are a challenge for automatic sleep staging.…”
mentioning
confidence: 99%